Impact of Withdrawal State Parties in 1998 Rome Statute of the Existence of International Criminal Court - Sandy Kurnia Christmas (Nagari Law Review, 2020)
The International Criminal Court is an international criminal justice institution established in the context of struggle against impunity. Eighteen years of operation of the ICC since 2002, ICC experienced a case where the state it one by one withdraw from membership, such as South Africa, Burundi, Gambia and the Philippines, which is due to the inclusion of ICC investigations related to these state as well as several reasons related to the existence of discriminatory ICC judicial operations patterns. What is the implementation of ICC legal norms by state parties, and how the impact on the existence of ICC is what will be discussed in this study. The research method used is Socio-Legal Research, which examines the relationship between juridical and political aspects. The results of this study conclude some evidence related to the implementation of ICC legal norms by withdrawing party states, such as the background to ratifying the Rome Statute 1998, the implementation of the law, and the reasons for withdrawing the country, as well as some juridical and political impacts affecting the existence of the ICC.